Hepatitis B Core Particle as a Display Platform for Foreign Epitopes - Yap, Wei Boon (2011)
Hepatitis B core (HBc) particle is a useful display platform for foreign epitopes due to its high immunogenicity and stability. HBc small and large particles are made up of 180 and 240 subunits of hepatitis B core antigen (HBcAg) with triangulation numbers, T=3 and T=4, respectively. The foreign epitopes are presented preferentially at the amino (N), carboxy (C) terminus or the immunodominant region of HBcAg without disturbing the formation of HBc particles. The effects of N-terminally inserted peptides with various lengths (14, 17, 22 and 25 amino acid residues) were first investigated in this study. A polyhistidine tag was inserted at the N-terminus of HBcAg with or without extraneous peptide linkers. The His-tagged HBc particles were purified with an IMACbased column. The yield improved with an increase in the length of N-terminal extensions. His--L-HBcAg carrying 20 extraneous amino acids at the N-terminus of HBcAg, was bound by anti-His monoclonal antibody and showed the highest colour intensity in the ELISA. The antigenicity of HBc particles was barely affected by the Nterminal insertion and they were reactive against an anti-HBc monoclonal antibody and human anti-HBc antisera. In addition, they formed virus-like particles with an average diameter of about 30 nm when observed under a transmission electron microscope (TEM). In order to authenticate the application of His-tagged HBc VLPs as an alternative diagnostic reagent in HBV infections, His--L-HBcAg was purified in substantial amount with immobilized metal affinity-expanded bed adsorption chromatography (IMA-EBAC). IMA-EBAC allows a single-step purification of His-tagged HBc particles directly from the unclarified Escherichia coli lysate. The duration needed in the protein purification process using IMA-EBAC is shorter (from two to three hours) than sucrose density gradient ultracentrifugation which requires two to three days. The yield of purified His-tagged HBcAg was shown to be 100-fold higher than that obtained with sucrose density gradient ultracentrifugation. An optimal adsorption of His-tagged HBc VLPs to the Streamline Chelating adsorbent was achieved at pH 8.0. The majority of the host cell proteins were eliminated by using wash buffers A (pH 8.0) and B (pH 6.0) supplemented with 10% (v/v) glycerol and 50 mM imidazole, respectively. Approximately 56% of the His-tagged HBc particles were recovered from the bacterial homogenate at pH 7.0 by using 500 mM imidazole and 1.5 M NaCl. The purified Histagged HBc particles remained antigenic and intact throughout the entire protein purification and they also formed HBc particles (30 nm) as verified by TEM. This implies that the purified His-tagged HBc VLPs can be a potential reagent in the diagnosis of HBV infections. The C-terminal region of the nucleocapsid (N) protein of Nipah virus, namely NP401-532,is vulnerable to bacterial proteases. Since HBc particle is highly stable and antigenic, NP401-532 was displayed at the N-terminus (NP401-532HBc) and the immunodominant loop (HBc79-80NP401-532) of HBc protein. NP401-532HBc and HBc79-80NP401-532 showed improved stability compared to that of NP401-532 when subjected to proteinase K treatment. In responses to the anti-NiV antisera, the antigenicity of the N-terminally inserted NP401-532 was enhanced whereas NP401-532 presented at the immunodominant loop was only detectable in its denatured form. The N-terminus of HBc protein is therefore preferable to its immunodominant loop with regard to the enhanced stability of the C-terminal domain of NiV N protein.